Sustainable transportation infrastructure investments and mode share changes: A 20-year background of Boulder, Colorado. (January 2015) - Henao, Alejandro; Piatkowski, Daniel; Luckey, Kara S.; Nordback, Krista; Marshall, Wesley E.; Krizek, Kevin J.
Abstract: This case study examines transportation infrastructure investments along with data revealing mode share in order to highlight correlations between investments in sustainable transportation infrastructure ('supply') and patterns of non-automobile mode share ('demand'). The analysis assesses data from Boulder, Colorado, a city that has made substantial efforts to improve its multi-modal transportation infrastructure and services by investing in pedestrian, bicycle, and transit infrastructure and services. We aim to describe connections between supply and demand by measuring two phenomena: the extent of transportation infrastructure investments supporting pedestrian, bicycle, and transit modes made between 1990 and 2009 and the share of these modes during the same 20 years period. Results illustrate an overall increase in transit and bicycle mode share and a decrease in single occupancy vehicle share, with consistent pedestrian share. We conclude that Boulder's investments in improving mode choices through new infrastructure and services supporting non-automobile modes are associated with increasing share of non-automobile modes. This is despite national trends that indicate an increasing automobile mode share. Regardless of the reasons for the positive trends experienced in Boulder, the presence of robust pedestrian, bicycling, and transit infrastructure has clearly coincided with evolving travel preferences. Boulder therefore serves as an example for other cities desiring to focus on developing policies and infrastructure that expand the availability of non-automobile modes. Highlights: This paper highlights correlations between transportation infrastructure investments and patterns of non-automobiles mode share. Boulder invested heavily in walking, cycling, and transit and saw a return on its investment with a reduction in SOV mode share. Bicycling and transit mode shares showed a marked increase between 1990 and 2009. Walking rates have increased in accordance with population growth. The presence of robust non-auto infrastructure has supported evolving travel preferences.